A Study On The Pattern And Distribution of Skull Fractures In Fatal Road Traffic Accidents (Indian Journal of Forensic Medicine & Toxicology, 2024)
Introduction: Road traffic accidents (RTA's) are a leading cause of mortality and a serious injury world wide, with skull fractures frequently emerging as a significant consequence of such incidents. The pattern and distribution of skull fractures can provide valuable insights into the mechanisms of injury and the severity of accidents. Understanding these patterns is crucila for improving both preventive measures and clinical responses.Materials and methods:This is aretrospective cross-sectional study of one year duration.All the cases of road traffic accident deaths with skull fractires were included in the study. A total of 342 cases of death due to fatal RTA were present and 140 cases had skull fractures.Results: The commonest site of fracture was the vault, observed in 64.28% of the cases. In fractures involving single bone of vault, frontal bone fractures were seen in the highest number of cases, in 29 cases(32.22%). The  MCF was the most commonly involved area in the base of the skull fractures, observed in 7.14% of the cases.Conclusion: A substantial amount of financial burden is produced on the family of   the deceased, on the health care system and as well as on the economic output of the country. Therefore, measures should be sought to reduce the RTA's as a number of positive and correct interventions can bring down their number.
Keywords: skull fractures, road traffic accidents, two-wheelers